Pengaruh Kepemimpinan Transformasional dan Budaya Sekolah terhadap Perilaku Inovatif Guru di SD Gugus 1 Kecamatan Gunung Talang : Penelitian - Yefrineng Delastri; Suswati Hendriyani; Elda Herlina; Asmendri; Isra Nurmai Yenti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the influence of transformational leadership and school culture on the innovative behavior of teachers at Elementary School Cluster 1, Gunung Talang District. This study uses a correlation research type with quantitative methods. The population in this study were 114 teachers at Elementary School Cluster 1, Gunung Talang District. The sampling technique was taken using a simple random sampling technique. The research sample numbered 53 people. Validity and reliability tests were tested with a significance level of 0.1 (10%). The questionnaire used was a closed questionnaire. To analyze the research data, an analysis technique was used by conducting a classical assumption test as a prerequisite test, then conducting simple linear regression, and multiple linear regression. Researchers used SPSS version 25 in data processing. The results showed that there was a significant influence of transformational leadership on teachers' innovative behavior. This was indicated by a sig value <0.1 for the t-test (partial). Furthermore, the second finding proved the influence of school culture on teachers' innovative behavior, also obtained from a sig value <0.1 with the t-test (partial). Then the final finding obtained a significant influence of transformational leadership and school culture on the innovative behavior of teachers at Elementary School Gugus 1, Gunung Talang District, obtained based on a simultaneous test or F test, with a sig value <0.1. The implication of this study is that school principals need to adopt a charismatic leadership approach, inspirational motivation, intellectual simulation, individual consideration and care for individual teacher needs. This will create higher motivation for teachers to behave innovatively in teaching which will improve the quality of education.